BRAF Mutation Analysis is a Valid Tool to Implement in Lynch Syndrome Diagnosis in Patients Classified According to the Bethesda Guidelines. Issue 3 (May 2014) - Molinari, Francesca; Signoroni, Stefano; Lampis, Andrea; Bertan, Claudia; Perrone, Federica; Sala, Paola; Mondini, Patrizia; Crippa, Stefano; Bertario, Lucio; Frattini, Milo
Aims and Background: Lynch syndrome (LS) is clinically defined by the Amsterdam criteria (AC) and by germline mutations in mismatch-repair (MMR) genes leading to microsatellite instability (MSI) at the molecular level. Patients who do not fulfil AC are considered suspected-Lynch according to the less stringent Bethesda guidelines (BG) and should be tested for MSI and MMR germline mutations. BRAF mutations have been proposed as a marker to exclude LS because they are generally absent in LS patients and present in sporadic colorectal cancer (sCRC) with MSI due to promoter hypermethylation of the MLH1 gene. Our aim was to verify whether BRAF mutations may improve the criteria to select patients for germline MMR mutation assessment. Material and Methods: We analyzed 303 formalin-fixed paraffin-embedded CRC samples including 174 sCRC, 28 patients fulfilling AC, and 101 suspected-Lynch patients fulfilling BG. We analyzed MSI and BRAF mutations in all CRC samples. MLH1, MSH2 and MSH6 germline mutations were investigated in MSI patients fulfilling AC or BG. Results: sCRC samples showed MSI in 20/174 (11%) cases. BRAF mutations were detected in 10/174 (6%) sCRC cases and were significantly correlated with MSI (P = 0.002). MSI was observed in 24/28 (86%) Amsterdam cases which were BRAF wildtype. MMR gene mutation was detected in 22/26 (85%) AC cases, all showing MSI. Suspected-Lynch cases carried MSI in 41/101 (40%) and BRAF mutations in 7/101 (7%) cases. MMR gene mutation was detected in 13/28 (46%) evaluable MSI patients of this group and only in cases characterized by a wild-type BRAF gene. Conclusions: The prevalence of BRAF mutations in CRC patients is not high but extremely correlated with MSI and risk categories as BG, whereas they are absent in LS patients. BRAF mutation detection can reduce the need for MMR gene analysis in a small (but not negligible) proportion of MSI patients (7%), with a positive impact on the financial and psychological costs of unnecessary tests.